High carrier frequency of a nonsense p.Trp230* variant in HSD3B2 gene in Ossetians - Makretskaya, Nina; Kalinchenko, Natalia; Tebieva, Inna; Ionova, Sofya; Zinchenko, Rena; Marakhonov, Andrey; Tiulpakov, Anatoly (Frontiers in Endocrinology, 2023)
Background: Congenital adrenal hyperplasia (CAH) caused by 3β-HSD deficiency is a rare form of congenital adrenal deficiency with an autosomal recessive type of inheritance. Previously we have demonstrated that a single nucleotide variant (SNV) p.W230X in the homozygous state is a frequent cause of CAH among the indigenous population of North Ossetia-Alania represented by Ossetians. Methods: Genotyping of the NM_000198.3:c.690G>A (p.W230X) variant was performed by Real-time PCR. 339 healthy individuals of Ossetian origin were included in the study. Allele frequencies, Fisher’s confidence intervals (CI) were calculated using the WinPepi v. 11.65 software. Comparison of allele frequencies was performed with the z-score test for two proportions. Results: Eight heterozygous carriers of c.690G>A variant in HSD3B2 gene were detected in 339 samples investigated. The total allele frequency of p.W230X variant was 0.0118 (n=8/678, 95% CI=0.0051–0.0231). Accordingly, the heterozygous carrier rate was 0.0236 (n=8/339). The frequency of CAH caused by p.W230X variant in HSD3B2 in Ossetian population was 1:7183 or 13.9 per 100,000 (95% CI: 1:1874–1:38447 or 3–53 per 100,000). Conclusion: The results demonstrate high frequency of p.W230X variant in Ossetians, which is most likely attributed to a founder effect.